Interconnecting Equitable and Prosperous Teaching-Learning Transitions and Transformations within the Digital Learning Framework - Jalaluddin Rumi; Asmirinda Resa; A. Fatimah Nurhikmah; Muh. Fillah; Muh. Gazali; Andi Aljabar (Edumaspul: Jurnal Pendidikan, 2024)
Studies on the main problems of Indonesian Education essentially highlight the educator's capability, professionality, and creativity. The fundamental problem lies in the reproduction and recruitment of educators themselves from the start. The problem becomes more complicated due to the acceleration of digital learning-based learning management systems synchronously/asynchronously, particularly in primary education as the foundation. This is also an observation and concept for the Kurikulum Merdeka implementation to overcome the education crisis through Merdeka Belajar policies, especially the Guru-Sekolah Penggerak program, the Merdeka Berbudaya media, the Merdeka Mengajar platform, and the Kampus Mengajar pattern. Such conditions are the focus of the study to assess opportunities for digital transformation in the teaching and learning process in elementary school and PGSD based on educators' perspectives on the students' characteristics and tendencies. This study uses a diagnostic case study method to examine the results of reports from related research institutions representatively and interpretively using internet searching techniques to be analyzed using critical discourse analysis to maintain the data commensurability. The report from the RISE Program in Indonesia, INOVASI, UNICEF Indonesia, SMERU Research Institute, and APJII then emphasized that strengthening educator competency, deepening curriculum flexibility, developing digital skills of educators and students, as well as improving teaching and learning platforms and school digital connectivity that focuses on an equitable education ecosystem is a challenge to respond the world education transformation. The results conform with OECD and UNESCO recommendations for embodying an equal and prosperous educational future. Hence, the Merdeka Belajar transition in Dikdas must become the basis for joint study to ensure the direction and realm of the transformation of Indonesian education.